Emerging biomaterials and bio-nano interfaces in pulmonary hypertension therapy: transformative strategies for personalized treatment - Chen, Xiaofa; Xu, Lina; Shi, Haiyan (Frontiers in Bioengineering and Biotechnology, 2025)
Pulmonary hypertension (PH) is still an aggressive and progressive illness with vascular remodeling and right heart failure despite the therapeutic advances made in the recent past. Biomaterials offer an attractive route to break the current therapeutic paradigms by inducing vascular repair, facilitating drug targeting, and allowing dynamic regeneration of tissue. This review taking an integrated approach investigates the revolutionary role played by novel biomaterials and bio–nano interfaces in PH treatment. We classify and evaluate several classes of biomaterial platforms including natural polymers, scaffolds based on synthetic polymers, extracellular vesicles (EVs), and stimulus-responsive systems with an emphasis on both underlying mechanisms and clinical relevance. We further address the progress made in artificial intelligence (AI)-based biomaterials and in integrating multi-omics tools to provide patient-tailored therapy. We finally touch on the ongoing limitations and enumerate future directions required to take forward biomaterial-based therapies towards clinical reality.